Bottom-up modelling of the Italian municipal waste generation: Model set-up, validation and pathways towards 2040. (10th July 2022) - Premoli Vilà, Lidia; Trabucchi, Andrea; Ferrè, Lorenzo; Grosso, Mario; Borgarello, Marco; Besagni, Giorgio
Abstract: The residential sector contributes to about 17% of the total waste generation in Italy. The main objectives set by the European and Italian governments regarding the waste sector include the promotion of reuse, recycling, and recovery, listed in order of importance; therefore, it is crucial to achieving, among others, a sufficient waste management capacity at the national level to accomplish such targets. In this context, a new approach to estimating and forecasting waste generation is introduced, based on bottom-up modelling to estimate the past and future Italian municipal waste generation. The modelling approach builds upon microdata describing the household expenditure behaviours supplied by the National Institute of Statistics. The assessment was carried out by dividing Italy into six macro-regions. The model was then validated by comparing the results with the historical aggregated official waste generation data. Lastly, a socio-demographic model has been applied to predict the trends of the various waste fractions due to the expected variation in the population, considering four different scenarios from 2019 to 2040. Results show the model's good performance, with relative errors below 5% at the national average concerning the historical data. The forecast of future trends gives a comprehensive picture of the effect of different waste management strategies. Highlights: A bottom-up model of the Italian municipal waste generation is presented. The model is validated considering global perspectives. Forecastings, based on socio-demographic projections are presented.